Osteoimmunopathology in HIV/AIDS: A Translational Evidence-Based Perspective. (21st May 2011) - Barkhordarian, André; Ajaj, Reem; Ramchandani, Manisha H.; Demerjian, Gary; Cayabyab, Riana; Danaie, Sohrab; Ghodousi, Nora; Iyer, Natasha; Mahanian, Nicole; Phi, Linda; Giroux, Amy; Manfrini, Ercolano; et al.
Abstract : Infection with the human immunodeficiency virus-1 (HIV) and the resulting acquired immune deficiency syndrome (AIDS) alter not only cellular immune regulation but also the bone metabolism. Since cellular immunity and bone metabolism are intimately intertwined in the osteoimmune network, it is to be expected that bone metabolism is also affected in patients with HIV/AIDS. The concerted evidence points convincingly toward impaired activity of osteoblasts and increased activity of osteoclasts in patients with HIV/AIDS, leading to a significant increase in the prevalence of osteoporosis. Research attributes these outcomes in part at least to the ART, PI, and HAART therapies endured by these patients. We review and discuss these lines of evidence from the perspective of translational clinically relevant complex systematic reviews for comparative effectiveness analysis and evidence-based intervention on a global scale.